Modern Orthodox Church History: A Bibliography of Works in Western Languages. - FAIREY, JACK (Greek Orthodox Theological Review)
A list of books and articles related to modern Eastern Orthodox Church history is presented including "The Eastern Orthodox Church: A Bibliography," by Dean Timothy Andrews, "An Orthodox Bibliography (in English)," by Nomikos M. Vaporis in "Greek Orthodox Theological Review," and "Intermarriage: Orthodox Perspectives," by Anton C. Vrame.